2006
DOI: 10.1074/mcp.m500427-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of the Extraembryonic Tissue from Cloned Porcine Embryos

Abstract: Cloned animals developed from somatic cell nuclear transfer (SCNT) embryos are useful resources for agricultural and medical applications. However, the birth rate in the cloned animals is very low, and the cloned animals that have survived show various developmental defects. In this report, we present the morphology and differentially regulated proteins in the extraembryonic tissue from SCNT embryos to understand the molecular nature of the tissue. We examined 26-day-old SCNT porcine embryos at which the sonog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 36 publications
4
38
0
Order By: Relevance
“…Histological analyses of 28 of the 38 scNT clones that died after birth revealed 11 had distinct histological anomalies, the most common of which was meningitis, followed by poor development of the elbow joint bone, flexor tendons, congestion, and Leydig cell hypoplasia (Park et al, 2004(Park et al, , 2005. As shown in our very recent report, the abnormal histopathologic findings of the deceased cloned pigs are closely associated with aberrant protein expression patterns (Park et al, 2005;Chae et al, 2006;Lee et al, 2007).…”
Section: Discussionmentioning
confidence: 76%
See 4 more Smart Citations
“…Histological analyses of 28 of the 38 scNT clones that died after birth revealed 11 had distinct histological anomalies, the most common of which was meningitis, followed by poor development of the elbow joint bone, flexor tendons, congestion, and Leydig cell hypoplasia (Park et al, 2004(Park et al, , 2005. As shown in our very recent report, the abnormal histopathologic findings of the deceased cloned pigs are closely associated with aberrant protein expression patterns (Park et al, 2005;Chae et al, 2006;Lee et al, 2007).…”
Section: Discussionmentioning
confidence: 76%
“…ROS levels increase gradually during early pregnancy, resulting in the apoptotic cell death of extraembryonic tissues (Chae et al, 2006). Very recently, we also reported that term placenta Fig.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations